2005
DOI: 10.1111/j.1547-5069.2005.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Decision‐Making Among HIV‐Positive Couples in Taiwan

Abstract: HIV status was not the sole determinant of reproductive decisions made by HIV-positive couples. Rather, the Confucian value of filial piety drove the couples' reproductive decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For instance, in a study from Taiwan, Ko and Muecke (2005) describe the power of Confucian doctrines to privilege the interests of men over those of women when reproductive decisions are made. 'The Confucian value of the ''Three Obediences'',' they write, 'required women to obey their husbands' decisions' (Ko and Muecke, 2005, 45).…”
Section: Reproductive Decision-making In the Context Of Gender And Kimentioning
confidence: 99%
“…For instance, in a study from Taiwan, Ko and Muecke (2005) describe the power of Confucian doctrines to privilege the interests of men over those of women when reproductive decisions are made. 'The Confucian value of the ''Three Obediences'',' they write, 'required women to obey their husbands' decisions' (Ko and Muecke, 2005, 45).…”
Section: Reproductive Decision-making In the Context Of Gender And Kimentioning
confidence: 99%
“…Even though women may intend to address this issue ''when the time is right, '' McCoy (2005) noted that when HIV-infected individuals do not feel comfortable or supported by their health care providers, they do not raise all of their concerns. Ko and Muecke (2005) reported that reproductive health issues tend to be ignored by health professionals in HIV-infected couples unless the HIV infection was diagnosed during the pregnancy. Thus, gaps in communication on this important topic may occur because individuals are not comfortable or because providers fail to initiate conversation on conception practices.…”
Section: Discussionmentioning
confidence: 97%
“…The data reported in this study come from a more comprehensive study conducted in Southern Taiwan in 2002 13 . Couples were eligible for the study if 1) they were in a heterosexual intimate relationship in which at least one person was infected with HIV; 2) the female partner was between 20 and 45 years of age; 3) both partners had been informed of each other's HIV status; 4) they were confronting or had confronted reproductive decisions during pregnancy; and 5) they were able to communicate comfortably in Mandarin, Taiwanese dialect, or English (which were the languages of the first author who conducted the field work).…”
Section: Methodsmentioning
confidence: 99%